Possibilities and limitations of the use of total accruals models in the detection of earnings management - Michał Comporek (Zeszyty Teoretyczne Rachunkowości, 2018)
Although from the point of view of financial reporting, net profit (loss) is the accounting result of the difference between revenues and deductible (operating) expenses, this measure due to its interactive nature has a significant impact on individual behavior of capital market participants, being a positive or negative condition of their capital involvement in company. At the same time, the category of net financial result is highly susceptible to intentional shaping of its amount by adjusting the value of net profit (loss) to the beliefs, thoughts, wishes and desires of individual stakeholders of an economic entity. The main goal of the presented article is to bring closer the characteristics of methodological solutions emphasizing the importance of total accruals in the detection of earnings management phenomenon. The research hypothesis suggests that there is a low and clearly differentiated degree of goodness-of-fit of individual accrual-based models to empirical data. The verification of the stated hypothesis took place using six models of total accruals: the Healy model, the DeAngelo model, the Jones model, the Dechow et al. model, the Kothari et al. model and the Kasznik model. Empirical studies were conducted among public companies included in the stock indices WIG20, mWIG40 or sWIG80, whose shares have been traded on the stock market for at least 15 years in the period 19992016.